2020
DOI: 10.3390/insects11080501
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Affects Symbiont Abundance in Bemisia tabaci (Hemiptera: Aleyrodidae)

Abstract: Symbionts contribute nutrients that allow insects to feed on plants. The whitefly Bemisia tabaci Middle East-Asia Minor 1 (MEAM1) is a polyphagous pest that depends on symbionts to provide key nutrients that are deficient in the diet. Here, we established three whitefly populations on eggplants, cucumbers, and tomatoes and observed that they harbored the same symbiont taxa in different quantities. The amount of the primary symbiont, Portiera, decreased with increasing concentrations of host-plant essential ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…In whiteflies reared on hibiscus and tobacco, the most represented amino acids were Gln, Ala, and Pro (NEAAs) and Arg (EAA). Similar observations have been reported in MED individuals reared on tomato and poinsettia ( 62 , 63 ) and in the close relative species, MEAM1, on cotton, cucumber, eggplant, and tomato ( 63 65 ), which are also considered favorable hosts for MED and MEAM1 species ( 43 , 66 68 ). In whiteflies reared on lantana, five EAAs (Ile, Leu, Lys, Met, and Phe) and one NEAA (Glu) were more represented than in whiteflies reared on the two other plants.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In whiteflies reared on hibiscus and tobacco, the most represented amino acids were Gln, Ala, and Pro (NEAAs) and Arg (EAA). Similar observations have been reported in MED individuals reared on tomato and poinsettia ( 62 , 63 ) and in the close relative species, MEAM1, on cotton, cucumber, eggplant, and tomato ( 63 65 ), which are also considered favorable hosts for MED and MEAM1 species ( 43 , 66 68 ). In whiteflies reared on lantana, five EAAs (Ile, Leu, Lys, Met, and Phe) and one NEAA (Glu) were more represented than in whiteflies reared on the two other plants.…”
Section: Discussionsupporting
confidence: 83%
“…A decrease of EAAs abundance in plants has been associated with an increase of “ Ca. Portiera” relative amount ( 65 ), possibly to meet the host metabolic demand. In our study, both P- and S-symbionts densities were higher on lantana.…”
Section: Discussionmentioning
confidence: 99%
“…After the third generation, the BPH gradually adapted to resistant plants as the number of YLS increased. Similarly, in previous studies on Bemisia tabaci, it was found that the number of symbionts in Bemisia tabaci populations from different plants fluctuated significantly before the third or fourth generation, after inoculation on different plants, and there was no significant change after that [42]. It can be seen that there seems to be a relationship between the variation of YLS and resistant rice varieties.…”
Section: Discussionsupporting
confidence: 71%
“…The tannins are endogenous inhibitors of the growth of numerous species of pests by negatively effecting the metabolism of insects [64]. Sap sucking pests such as whiteflies and aphids make use of symbionts for their essential amino acids [65,66]. Symbiotic essential amino acids provisioning or supplementation has also been found in the American cockroach and Cerambycid [67,68].…”
Section: Implications For Pest Managementmentioning
confidence: 99%